MOTIVATION, JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT OF PROGRAM MANAGERS WITH HEALTH CARE COVERAGE AT PUBLIC HEALTH CARE IN BONDOWOSO - Putri, Melati Laksni; Witcahyo, Eri (Tadulako University, 2018)
Background & Objective: Based on Bondowoso’s Performance Assessment of Public Health Care in 2014 through 2016, there is one aspect of the Performance Assessment of Public Health Care that always belongs to the low performance, it is the aspect of health care coverage. The level of health care coverage significantly affect life expectancy. Life expectancy is one indicator in determining backward region. Based on Presidential Decree No. 131 in 2015 Bondowoso established as a backward region in East Java at the first place. This study aimed to analyze the correlation between motivation, job satisfaction and organizational commitment of program managers with health care coverage at Public Health Care in Bondowoso 2017. Material and Method: This study used analytic research with cross–sectional approach. Population of this research were 101 program managers with total sample were 81 respondent. Result: An association between motivation (p value = 0.000 <0.05), job satisfaction (p value = 0.000 <0.05) and organizational commitment (p value = 0.007 <0.05) with health care coverage. Conclusion: There is a correlation between Motivation, Job satisfaction and Organizational Commitment with Health Care Coverage